COMPUTED TOMOGRAPHIC CHARACTERISTICS OF ODONTOGENIC NEOPLASMS IN DOGS. Issue 2 (18th September 2013) - Amory, Joseph T.; Reetz, Jennifer A.; Sánchez, Melissa D.; Bradley, Charles W.; Lewis, John R.; Reiter, Alexander M.; Mai, Wilfried
<x xml:space="preserve">Abstract</x> Odontogenic neoplasms are locally invasive oral tumors in dogs. The purpose of this retrospective study was to describe CT characteristics for varying histopathologic types of canine odontogenic neoplasms. A board‐certified veterinary radiologist who was unaware of histologic findings reviewed and scored imaging studies. A total of 29 dogs were included in the study. Twenty‐three of these dogs had concurrent dental radiographs. The most common CT characteristics for all tumor types were a direct association with or in the region of multiple teeth in 96.4% (27/28), contrast enhancement in 96.3% (26/27), alveolar bone lysis in 93.1% (27/29), and mass‐associated tooth displacement in 85.2% (23/27). Mass‐associated cyst‐like structures were identified in 53.6% (15/28) and were only present in tumors containing odontogenic epithelium. Canine acanthomatous ameloblastomas (n = 15) appeared as extra‐osseous (10/15) or intra‐osseous (5/15) masses. Intra‐osseous canine acanthomatous ameloblastomas were more likely to have mass‐associated cyst‐like structures and were subjectively more aggressive when compared with extra‐osseous canine acanthomatous ameloblastomas. Amyloid‐producing odontogenic tumors (n = 3) had subjectively uniform CT imaging characteristics and consisted of round soft tissue and mineral attenuating masses with multiple associated cyst‐like structures. Fibromatous epulides of periodontal ligament origin (n = 4) were contrast enhancing extra‐osseous masses that were rarely referred for CT examinations and 25% (1/4) were not visible with CT. Other odontogenic tumors were less represented or had more variable CT imaging characteristics. Mass‐associated tooth destruction was appreciated more often with dental radiographs and extra‐oral tumor extension was identified more often with CT.